Human Genetic Adaptations to Environmental Pressures: The Role of Migration in Evolutionary Success - Amir Jalali; Majid Komijani; Saja Al-Sailawi (Journal of Genetic Resources)
Human evolution has been shaped by complex interactions between genetic variation, environmental pressures, and human migration. This review explores the mechanisms by which genetic adaptations have enabled humans to survive and thrive across diverse ecological contexts. The focus is on how migration has contributed to the spread and maintenance of beneficial alleles, influencing contemporary patterns of genetic diversity. We critically examine genetic adaptations associated with resistance to infectious diseases such as malaria, leprosy, and human immunodeficiency virus (HIV), as well as the evolution of immune responses shaped by transitions between tropical and temperate climates. Adaptations to high-altitude environments, including changes in oxygen regulation through genes like EPAS1 and EGLN1, are discussed alongside dietary shifts such as lactase persistence and their connection to cultural practices like dairy consumption. Other examples include genetic variants that promote vitamin D synthesis in northern latitudes and variants linked to energy conservation in historically food-scarce environments. To ensure scientific rigor, we applied strict inclusion criteria focused on relevance, statistical significance, replication across populations, and biological plausibility. Studies were selected independently of authorship and drawn from large-scale genomic datasets representing diverse populations. The review also considers microbial and molecular markers, such as those derived from Helicobacter pylori phylogeography, which offer additional insights into human migration histories. Rather than presenting a summary of isolated findings, this review integrates results across evolutionary domains to clarify how environmental challenges and human movement have jointly shaped the human genome. By adopting an interdisciplinary approach, combining insights from genomics, anthropology, and population biology, the study highlights how adaptation and migration have contributed to present-day genetic diversity. This perspective supports a broader understanding of human resilience and the evolutionary processes underlying global genetic variation.